Peran Financial Technology (Fintech) Dalam Meningkatkan Literasi Dan Inklusi Keuangan Di Kalangan Mahasiswa Indonesia - Umar (CV. SINAR HOWUHOWU, 2025)
The development of Financial Technology (fintech) in Indonesia has grown rapidly, offering greater convenience in accessing financial services. University students, as active users of digital technology, are among the primary target groups benefiting from fintech innovation. This study aims to analyze the role of fintech in enhancing financial literacy and financial inclusion among Indonesian university students. A descriptive research approach was employed, drawing on literature reviews and analysis of previous studies. The results indicate that fintech significantly contributes to improving students’ understanding of financial management, digital financial products, and financial risk awareness. Moreover, fintech expands students’ access to formal financial services such as digital payments, online savings, and investment platforms. However, limited knowledge regarding digital security and the risks associated with online lending remains a major challenge. This study highlights the importance of collaboration among the government, the Financial Services Authority (OJK), educational institutions, and fintech providers to sustainably enhance financial literacy and inclusion among students.